Microbial Isolates and their Resistance Patterns at an Indian Teaching Hosptial - A Retrospective Study - Poojitha A; Sultana Gouhar; Bindu Madhavi V; N.Hanisha Gupta; Qamar U.B Siddiqui; Mustafa Afzal; Mohammed A. Ghufran (Universitas Padjadjaran, Indonesia, 2022)
Rapidly rising antibiotic resistance is a challenge to comprehensive patient care in all branches of medical science. A retrospective observational study was conducted to determine the antimicrobial resistance patterns in a tertiary care hospital for six months. The data was collected from laboratory test reports and patient case files using a structured data collection form. A total of 200 cases having a positive culture report were included in the study. Of these, 186 cases were identified to have gram-negative infections, and 14 had gram-positive infections. Escherichia coli (E. Coli) (47%) was the predominant isolate among gram-negative organisms, followed by Klebsiella (24.5%), Pseudomonas (7.55%), Enterobacter (6.5%), and Citrobacter (4.5%). All Gram-positive organisms E.coli, Klebsiella, Pseudomonas, Enterobacter have shown maximum resistance of 92.55%, 95.91%, 93.33%, and 76.92%, respectively, Ampicillin. E.coli has shown the least resistance to carbapenems (7.44%). Klebsiella demonstrated minimum reistance of 10.2% to cefotaxime, cefazolin and levofloxacin. Pseudomonas was completely sensitive to piperacillin-tazobactam. Enterobacter showed least resistance to gentamicin (3.07%) and piperacillin-tazobactam (3.07%). The primary gram-positive isolate, Enterococcus spp. (5.5%) mainly was resistant to ciprofloxacin (90.90%), followed by levofloxacin (81.81%), tetracycline (81.81%), and gentamicin (72.72%). E. coli was the most resistant organism in the present study. The study results would contribute to the development of an antibiogram at the study site.